The travels of a lone star tick. - Alderdice, J M (1998)
A lone-star tick, Amblyomma americanum, was found as a pedunculated lesion on the back of the arm of an 84 year old man in Northern Ireland. This was acquired on a visit to the USA. The tick is found mainly in Texas and the Ozark mountains of Missouri, with scattered foci in other parts of southern USA. It is the vector of Rocky Mountain spotted fever. As worldwide travel becomes increasingly common, exotic parasites make occasional appearances in northern Europe.